The combination of implanting with Revalor-200 and feeding zilmax increases subprimal meat yield of fed cows - S. Neill; T.T. Marston; M.J. Daniel; James J. Higgins; John A. Unruh; John R. Jaeger (Kansas Agricultural Experiment Station Research Reports, 2009)
Mature cows are culled from herds for reasons such as poor performance and failure to rebreed. When these cows are removed from the herd, they are typically in thin condition and potentially can be fed to gain weight and increase income. Previous research has shown that feeding cull cows high-energy diets can increase carcass weight, fatness, and meat yield. Management practices of implanting and feeding β-adrenergic agonists, repartitioning agents that favor protein deposition at the expense of fat deposition, have been shown to further improve performance and carcass yields. As reported elsewhere in this publication, carcasses from concentrate-fed cows implanted with Revalor-200 (Intervet Inc., Millsboro, DE) and fed Zilmax (zilpaterol hydrochloride; Intervet Inc.) had more muscling as indicated by larger ribeye areas than carcasses from grass-fed cows and both implanted and non-implanted concentrate-fed cows. These carcasses potentially would have increased subprimal meat yields. Therefore, the objective of this study was to determine the effects of concentrate feeding, implanting, and feeding Zilmax on subprimal meat yield of mature cows fed for 70 days.
Keywords: Cattlemen& #x27; s Day; 2009; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1010; Kansas Agricultural Experiment Station contribution; no. 09-168-S; Beef; Cattle; Zilmax; Revalor-200